Desain Perbaikan Perkerasan Kaku Akses Jalan PPKP dengan Metode AASHTO dan ESAL - Joshua Henry Frankestein Apituley; Muhammad Tegar Wijaya; Viktor Suryan (Teknik Sipil, Politeknik Negeri Ketapangg, 2026)
The road in front of the firefighting study program at the Palembang Aviation Polytechnic experienced serious damage in the form of transverse cracks and a 4.6 × 4.6 m collapse. This damage was caused by the frequent passage of heavy foam-tender vehicles during practice, disrupting operations and endangering user safety. This condition indicates the need for pavement capable of withstanding high dynamic loads in a limited area. This study aims to redesign the rigid pavement layer in the courtyard of the PPKP Poltekbang Palembang Building. Specific objectives include identifying the type and severity of damage, calculating traffic and vehicle loads (ESAL), and determining the optimal pavement thickness for structural repair. The research applied a quantitative approach with primary data from field observations and damage measurements, and secondary data from literature and PKP-PK vehicle specifications. Analysis was conducted using the AASHTO 1993 method with a focus on ESAL calculations to determine rigid pavement thickness. Results showed that damage was due to heavy foam tender traffic. The 20-year cumulative ESAL of 84.25 is considered low, but the high axle load requires a minimum 20 cm concrete slab for safety and optimal service life. This research provides technical recommendations for safe, efficient road repairs in campus areas with high dynamic loads.